Worldwide mobile wallet: a futuristic cashless system - Mumtaza, Qorina Mailil Husna; Nabillah, Shada Intishar; Amaliya, Sholikhatul; Rosabella, Yuveta; Hammad, Jehad Abdelhamid (Bulletin of Social Informatics Theory and Application, 2020)
The proliferation of the internet led to the emergence of new technology. Nowadays, many activities can be done online, such a payment. After Mobile Banking was introduced publicly, a new method for payment called mobile wallet that uses mobile application as a device appears. The ease caused by this technology should be the main reason for implementing this system on to daily basis. Nevertheless, in various countries, the usage rate of the cashless system remains uneven, caused by many factors, both from internal factors such as security risks and external factors such as the policies of the countries involved. This paper will evaluate worldwide online payment systems to determine the impact of online payment systems usage, both positive and negative. This paper will evaluate the factors that affect the introduction of m-payment. Several measurements, such as country with the highest and lowest cashless payment usage and the reasons were taken for this research so that the objectives to improve the system and increase the usage rate can be achieved.